Multidrug resistant Stenotrophomonas maltophilia: An emerging cause of hospital acquired infections in Assiut University Hospitals, Egypt - Daef, Enas Abdel Mageed; Elsherbiny, Nahla Mohamed; Thabit, Amany Gamal; Wageah, Ehsan Mohammad (International Journal of Infection Control, 2017)
Stenotrophomonas maltophilia is an emergent pathogen in health¬care facilities worldwide that is intrinsically resistant to many antibiotics. We aimed to determine the prevalence of S. maltophila causing health care associated infections (HAIs) and environmental contamination at the intensive care units (ICUs) of Assiut University Hospitals, the antibiotic resistance profiles, production of metallo-β-lactamases (MBLs) and detection of sul 2 gene. A total of 690 clinical samples and 4151 environmental samples were collected. S. maltophila isolates were identified and confirmed by detection of 16S rRNA-23S rRNA gene by PCR. Antimicrobial resistance was determined by Kirbey Bauer disc diffusion method and imipenem MIC by E test. The presence of MBLs were detected by combined disc test (CDT) and double disc synergy test (DDST). The presence of sul 2 gene was determined by PCR. S. maltophila caused 9.7% of HAIs in the ICUs mostly respiratory tract infections and 0.67% of environmental contamination . A high percentage of resistance was found for most of the studied antimicrobials including carbapenems. MBLs were detected in all imipenem resistant isolates and in variable percentages in imipenem sensitive isolates. The least resistance found was to trimethoprim sulfamethoxazole (SXT). All SXT resistant isolates harboured the sul 2 gene. Multidrug resistance was reported in 63.5% of isolates. S. maltophilia causes a considerable percentage of HAIs especially respiratory tract infections and environmental contamination in the ICUs. A high percentage is MDR. Trimethoprim-sulfamethoxazole is the single agent of choice for the treatment of S. maltophilia infections. The detection of sul2 gene and MBLs among isolates at our hospitals is alarming.